Estimation of the lower practical limit of aquatic plant coverage in intensive Chinese mitten crab (Eriocheir sinensis) rearing ponds using an unmanned aerial vehicle. (4th June 2019) - Shi, Linlin; Tian, Ting; Shen, Mingxing; Jin, Meijuan; Zhang, Qing; Zhang, Weiye; Lu, Changying
Abstract: Aquatic plants play important roles in the productivity of intensive Chinese mitten crab (CMC) rearing ponds. This study aimed to evaluate the lower limit of aquatic plant coverage (APC) in CMC ponds. A field investigation was conducted and unmanned aerial vehicle was used to estimate APCs. A follow‐on single factor experiment was performed to verify the results and evaluated the efficacy of APC values with 15%, 45%, 65% and 85% APC treatments. Average total nitrogen (0.81 mg/L), total phosphorus (0.06 mg/L), ammonium‐N (0.12 mg/L) and nitrate‐N (0.10 mg/L) met the grade II–IV standards for surface water quality in China in the investigations. Further, the use of an exponential decay model for water qualities and APCs indicated that an effective APC threshold was around 30%, and crab yields (1, 536 kg ha –1  year –1 ) significantly decreased by 19.2% if the pond APCs could not reach this threshold. Crab yields were also correlated with crab feed characteristics, and especially the level of fish meat that was used. The single factor experiment for APC again confirmed our APC value threshold via exponential model. Meanwhile, the water quality measurements of the 15% APC treatment were significantly larger than the other APC treatments, but the crab yield, individual weight and carapace length indeed decreased in this single factor experiment for APC. We therefore conclude that the empirical APC level of 60% is preferred, but that smaller APCs could be acceptable in intensive CMC ponds if an APC of at least 30% is maintained.